Feasting on Collaborations - Jajwalya R Karajgikar (Journal of Electronic Publishing)
Just as any delicious dish inspires awe, hearty collaborations are made of people coming together to bring projects to life, one recipe at a time. A food item contains multiple ingredients, features myriad styles of making, and reveals a diversity of piquant spices; so, too, are hearty collaborations made of people from various collegial expertise, research traditions, differing perspectives, life experiences, etc. In this zine, I invite you to consider the relationship between food and collaboration. Drawing on theories from anthropology, gastropoetics, literary studies, and critical making in the digital humanities, we can explore how gathering around food relates to labor and radical notions in a world shaped by silos of expertise at workplaces. In this moment in time of an uncertain world over several matters of contention, my social imperatives point me to this local community of my own: you, my colleague, my collaborator, my friend. I hope you will join me in celebrating these lighthouse beacons of celebrations over our work together.